Digital deforestation monitoring and control system: An innovative approach to the conservation of forest resources - Lukin Vladislav; Zolnikov Vladimir (BIO Web of Conferences)
This article presents the concept of an innovative digital system for monitoring and controlling deforestation, aimed at improving the efficiency of forest management and combating illegal logging. The system is based on the use of modern high-resolution satellite data and machine learning methods to analyze changes in forest cover. The paper describes the architecture of the proposed system, which includes modules for data collection, change analysis, classification and visualization. Special attention is paid to the potential advantages of the system, such as improving the accuracy and efficiency of detecting changes in forests. Possible problems and limitations in the implementation of the system are considered, including dependence on the quality of satellite images, requirements for computing resources and legal aspects. The proposed system has the potential to significantly improve the monitoring of forest resources, contributing to their conservation and sustainable use in the context of global climate change.